2023
DOI: 10.1101/2023.03.13.532152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted engagement of β-catenin-Ikaros complexes in refractory B-cell malignancies

Abstract: In most cell types, nuclear beta-catenin functions as prominent oncogenic driver and pairs with TCF7-family factors for transcriptional activation of MYC. Surprisingly, B-lymphoid malignancies not only lacked expression and activating lesions of beta-catenin but critically depended on GSK3B for effective beta-catenin degradation. Our interactome studies in B-lymphoid tumors revealed that beta-catenin formed repressive complexes with lymphoid-specific Ikaros factors at the expense of TCF7. Instead of MYC-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…We also showed that other validated small molecule GSK3α/β inhibitors do not share the anti-lymphoma properties of elraglusib and that GSK3A/B shRNA knockdown did not affect the elraglusib IC50 (17,18). Preprint data from Cosgun et al also reports broad cytotoxic effects of elraglusib in the absence of β-catenin or myc stabilisation suggesting it occurs without significant GSK3 inhibition (17,26). Together, these findings question the requirement for GSK3 inhibition in the mechanism of action of elraglusib.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that other validated small molecule GSK3α/β inhibitors do not share the anti-lymphoma properties of elraglusib and that GSK3A/B shRNA knockdown did not affect the elraglusib IC50 (17,18). Preprint data from Cosgun et al also reports broad cytotoxic effects of elraglusib in the absence of β-catenin or myc stabilisation suggesting it occurs without significant GSK3 inhibition (17,26). Together, these findings question the requirement for GSK3 inhibition in the mechanism of action of elraglusib.…”
Section: Discussionmentioning
confidence: 99%